Application of the Wigner-Function Formulation to Mesoscopic Systems in Presence of Electron-Phonon Interaction. Issue 1 (1998) - Jacoboni, C.; Abramo, A.; Bordone, P.; Brunetti, R.; Pascoli, M.
Abstract : A theoretical and computational analysis of the quantum dynamics of charge carriers in presence of electron-phonon interaction based on the Wigner function is here applied to the study of transport in mesoscopic systems. Numerical applications are shown for a) a wave packet scattering with phonons while crossing a potential profile and b) electrons scattering with phonons in a finite device with open boundary conditions.